(untitled) (Costos y Gestión, 2022)
The proposed methodology to design the value chain of photovoltaic panels produced by the Electronic Components company, Pinar del Río, Cuba, is aimed at supporting financial management, customer satisfaction and calculating management and profitability indexes that help better constant control of decision-making. The research is carried out from a referential methodological framework, with a view to its practical application, based on the study of different value chain methodologies. It is made up of stages, steps, activities and other elements taken from other methodologies such as: the ECLAC-GIZ Project, the Local Support Program for Agricultural Modernization in Cuba (PALMA) and the European Union and the Swiss Agency for Coopera[1]tion for the Development, the case of the mango chain in Santiago de Cuba, the tourism management model from the local government for municipalities with a tourist vocation (MVT) based on the value chain approach and the accounting management of ecosystem services in companies agroforestry with a value chain approach.